Finite difference scheme for a singularly perturbed parabolic equations in the presence of initial and boundary layers - Cordero, Nicolas; Cronin, Kevin; Shishkin, Grigorii; Shishkina, Lida; Stynes, Martin (Mathematical Modelling and Analysis, 2008)
The grid approximation of an initial‐boundary value problem is considered for a singularly perturbed parabolic reaction‐diffusion equation. The second‐order spatial derivative and the temporal derivative in the differential equation are multiplied by parameters å 2 1 and å 2 2, respectively, that take arbitrary values in the open‐closed interval (0,1]. The solutions of such parabolic problems typically have boundary, initial layers and/or initial‐boundary layers. A priori estimates are constructed for the regular and singular components of the solution. Using such estimates and the condensing mesh technique for a tensor‐product grid, piecewise‐uniform in xand t, a difference scheme is constructed that converges å‐uniformly at the rate O(N−2 ln2 N + N0 −1 ln N0 ), where (N + 1) and (N0 + 1) are the numbers of mesh points in x and t respectively. First Published Online: 14 Oct 2010